2020
DOI: 10.3390/plants9101394
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols Content in Capsicum chinense Fruits at Different Harvest Times and Their Correlation with the Antioxidant Activity

Abstract: The aim of this work was to investigate the changes of the content of polyphenols in fruits of Capsicum chinense Jacq. at different harvest times and their correlation with the antioxidant activity. Habanero pepper plants grown in black soil (Mayan name: Box lu’um) and harvested at 160, 209, 223, 237 and 252 post-transplant days (PTD) were analyzed. The results indicated that subsequent harvesting cycles decreased the content of total polyphenols, catechin, chlorogenic acid and ellagic acid, while the content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 33 publications
5
12
0
Order By: Relevance
“…Therefore, the genotypes that stood out in terms of agronomic performance (HNC-2, HNC-3, HNC-6, and HNC-7) and the content of bioactive compounds in the fruits (HNC-5, HNC-6, and HCC-8), will be used for the generation of inbred lines to obtain hybrids that can be cultivated and used in the agri-food industry in the southeastern region of Coahuila. Previous studies have documented that there is a strong correlation between total phenol content and antioxidant activity, which could be due to the high content of flavonoid-type compounds that contribute to the antioxidant activity in different species of chili peppers [68,69]. Therefore, the results of this research support the notion that the antioxidant activity is strongly influenced by the concentration of polyphenols in the evaluated habanero pepper fruits.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Therefore, the genotypes that stood out in terms of agronomic performance (HNC-2, HNC-3, HNC-6, and HNC-7) and the content of bioactive compounds in the fruits (HNC-5, HNC-6, and HCC-8), will be used for the generation of inbred lines to obtain hybrids that can be cultivated and used in the agri-food industry in the southeastern region of Coahuila. Previous studies have documented that there is a strong correlation between total phenol content and antioxidant activity, which could be due to the high content of flavonoid-type compounds that contribute to the antioxidant activity in different species of chili peppers [68,69]. Therefore, the results of this research support the notion that the antioxidant activity is strongly influenced by the concentration of polyphenols in the evaluated habanero pepper fruits.…”
Section: Discussionsupporting
confidence: 83%
“…and r = 0.89, respectively) and the antioxidant capacity measured by DPPH, ABTS and FRAP (Figures 5,6) suggests that the higher values of phenolic compounds in HNC-6, HNC-5, and HCC-8 are related to a higher antioxidant capacity. Previous studies have documented that there is a strong correlation between total phenol content and antioxidant activity, which could be due to the high content of flavonoid-type compounds that contribute to the antioxidant activity in different species of chili peppers [68,69]. Therefore, the results of this research support the notion that the antioxidant activity is strongly influenced by the concentration of polyphenols in the evaluated habanero pepper fruits.…”
Section: Antioxidant Capacitysupporting
confidence: 83%
“…These compounds are also responsible for strong antioxidant capacity. The results of many studies confirmed the positive correlation between the antioxidant activity and the content of phenolic acids or other polyphenols [42,52]. Therefore, in our study, we decided to evaluate the antioxidant activity of the analyzed extracts incorporated into BC.…”
Section: Discussionsupporting
confidence: 61%
“…On the other hand, in the case of some plant substances, their greater accumulation in the skin is preferred, as, through their antioxidant activity, they could show among others, the anti-aging effect [74]. It is obvious, that apart from the polyphenols, the skin may penetrate the whole pool of antioxidants contained in plants, however, phenolic acids constitute a significant part of skin-permeable compounds [42,52].…”
Section: Discussionmentioning
confidence: 99%
“…The ABTS radical assay was performed according to the method adopted by Oney-Montalvo 28 with some modifications. A 20 µL aliquot of the extract was mixed with 170 µL ABTS solution in a 96-well microplate.…”
Section: Methodsmentioning
confidence: 99%